Examining Absorptive Capacity in Supply Chains: Linking Responsive Strategy and Firm Performance. Issue 4 (October 2015) - Dobrzykowski, David D.; Leuschner, Rudolf; Hong, Paul C.; Roh, James J.
<x xml:space="preserve">Abstract</x> Information management is a core supply chain activity that is increasing in importance as firms strive to become more responsive to growing customer demand for innovative products. However, effective processing of information from customers and suppliers remains a struggle for most firms. Absorptive capacity provides a useful view of information processing activities, but the current understanding of how firms use it to improve performance and why some firms seem to develop it while others do not remains unclear. This study is grounded in information processing theory, and examines the role of absorptive capacity in linking a firm's responsive strategy and performance. We test a structural equation model on data from 711 manufacturing firms, and validate our results on a second sample of 677 firms. Our study makes three major contributions by providing evidence that: (1) absorptive capacity is motivated by a firm's responsive strategy; (2) it fully mediates the relationship between responsive strategy and firm performance, indicating that absorptive capacity is a necessary competence for firms that aim to deliver innovative products to customers; and (3) the relationship between responsive strategy and absorptive capacity is U‐shaped, indicating that when firms attempt to blend efficient and responsive strategies, their ability to develop absorptive capacity is diminished.